Розробка програматора для радіостанцій Motorola GM-300, M-120 - Головенко, О. О. (ХНУРЕ, 2024)
The Motorola GM-300 and M-120 radios have a wide frequency range that allows them to work in a variety of conditions and environments. However, to use these stations effectively, you need to be able to program their settings, including frequencies and signal parameters. This report describes the development of a programmer specifically designed for these radios. This programmer will allow users to easily and efficiently program the settings of their radio stations, which will ensure optimal operation and high quality of communication. In addition, the programmer also provides the possibility of rebroadcasting the signal, which significantly expands the range of radio stations.
Keywords: програматор; радіостанція Motorola GM-300